FACTORS IMPACT ON DIRECTOR CAPABILITIES TO RUN VILLAGE-OWNED ENTERPRISES (BUMDESA) - Ihwan Sudrajat (Jurnal Ilmiah Wahana Bhakti Praja, 2024)
The objective of this study is to present the perspectives of District Heads (Camat), regarding to the existence of BUMDesa and the impact factors on directors capabilities to run BUMDesa. These factors are primarily related to the characteristics of the BUMDesa directors, including their competence, capability, and social culture. This research employs a combination of quantitative descriptive statistics and qualitative methods. The subjects of the study are Camats selected through convenient sampling. The survey was conducted using measurement tools developed by the researcher, based on the theory of Naminse, Zhung, and Zhu (2019), which comprises aspects of competence, capability, and socio-cultural factors. The results show that the number of active BUMDesa in the district is less than 50%; the majority of BUMDesa administrators have a high school education, with only a small proportion (22%) holding a bachelor's degree. Capability or work experience prior to becoming a director is more critical than educational level. Additionally, most BUMDesa directors have other jobs, predominantly as entrepreneurs. This dual-role profession prevents BUMDesa directors from fully focusing on the development of BUMDesa. The influence of the village head is significant in shaping the existence of BUMDesa, with village heads playing a vital role in determining BUMDesa administrators. This role can be both a hindrance and a support. Successful BUMDesa are generally backed by strong support from the village heads. District heads have not yet optimally performed their primary duties and functions, but there is great enthusiasm among them to enhance guidance for BUMDesa, especially in initiating the establishment of joint BUMDesa. Keywords: competence, capability, and social culture